ISLAM DAN KEBANGSAAN: TEORI DAN PRAKTIK GERAKAN SOSIAL ISLAM DI INDONESIA (Studi atas Front Umat Islam Kota Bandung) - Abdul Jamil (Harmoni, 2013)
Front Umat Islam (FUI) is one of religious social movements in West Java that is active in conducting many mass mobilizations to oppose matters that are considered deviating from Islamic teachings. Based on a qualitative approach, it is understood that the FUI can be regarded as a deviant social movement due to its approach in forcing the will of other believers whom they regard as defaming religion (Islam). However, their ideological and national concepts are moderate; politically they do not offer radical alternative to the current socio-political reality, FUI still respects the four pillars of Indonesian nationality, namely Pancasila, NKRI, UUD 1945, and Bhineka Tunggal Ika. Referring to the theory of social movement, as a movement that has a political objective and social capital, the activities of FUI are acceptable. FUI conducts social negotiation to realize social order in public sphere, namely Bandung which is religious.